Scientific Committee of the XIII International Tourism Congress - (:unkn) unknown (My University, 2026)
The International Tourism Congress is the annual scientific meeting of the Centre for Tourism Research, Development, and Innovation (CiTUR). The XIII edition (that will occur in October 2021) will be organised by CiTUR's Estoril hub and supported by the Estoril Higher Institute for Tourism and Hotel Studies (ESHTE)